2017
DOI: 10.1016/s2214-109x(17)30072-4
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone-delivered reminders and incentives to improve childhood immunisation coverage and timeliness in Kenya (M-SIMU): a cluster randomised controlled trial

Abstract: SummaryBackgroundAs mobile phone access continues to expand globally, opportunities exist to leverage these technologies to support demand for immunisation services and improve vaccine coverage. We aimed to assess whether short message service (SMS) reminders and monetary incentives can improve immunisation uptake in Kenya.MethodsIn this cluster-randomised controlled trial, villages were randomly and evenly allocated to four groups: control, SMS only, SMS plus a 75 Kenya Shilling (KES) incentive, and SMS plus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
153
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(177 citation statements)
references
References 34 publications
6
153
6
Order By: Relevance
“…The current study was not design to assess factors associated to low coverage but, other studies conducted in similar settings indexed parental ignorance, parental level of education, limitations due to geographical and cultural accessibility, outreach and door-to-door programs and poverty as key contributors to low immunization coverage [1][2][3]. Information and communication technology and incentives vaccination strategies for reminder has proven to be effective in improving childrens' access to EPI but have not been integrated in the routine EPI strategy [24][25][26][27][28][29]. On this note, the efficiency of these strategies should be assessed in the Cameroon context.…”
Section: Discussionmentioning
confidence: 94%
“…The current study was not design to assess factors associated to low coverage but, other studies conducted in similar settings indexed parental ignorance, parental level of education, limitations due to geographical and cultural accessibility, outreach and door-to-door programs and poverty as key contributors to low immunization coverage [1][2][3]. Information and communication technology and incentives vaccination strategies for reminder has proven to be effective in improving childrens' access to EPI but have not been integrated in the routine EPI strategy [24][25][26][27][28][29]. On this note, the efficiency of these strategies should be assessed in the Cameroon context.…”
Section: Discussionmentioning
confidence: 94%
“…However, the findings of recent reviews on the potential for mobile phone interventions, including daily text message reminders, to influence patient treatment outcomes were inconclusive and the authors repeatedly highlighted the lack of high‐quality data available for analysis . Outside of TB care, a recent study in Kenya evaluating text message reminders for increasing vaccination coverage showed no increase in overall vaccination rates in the group only allocated to receive reminders . These ‘nudge’ interventions have historically been popular with policy makers partly because they are perceived to be wide‐reaching and low‐cost.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to providing automated mobile phone reminders and compliance-linked incentives, the platform also served as a standardized, cloud-based immunization record system that linked to positive identification (biometrics) of individual children. Unlike previous studies in which researchers restricted recruitment to young infants (≤6 weeks old), 10,11 we recruited all eligible children 24 months and younger to measure improvement in primary immunizations in young infants recruited early in their lives as well as partially immunized toddlers. This study was performed in a rural, low-income area with low literacy rates; 83.6% of mothers had no schooling.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, researchers have assessed the role of mobile messaging and/ or compliance-linked incentives to improve health indices 8 and immunizations in young children. 9 -12 Gibson et al 11 recently reported that mobile phone reminders coupled with mobile phone-delivered monetary incentives significantly improved immunization coverage and timeliness in rural western Kenya, a community with high baseline (86%) immunization coverage.…”
Section: What This Study Addsmentioning
confidence: 99%
See 1 more Smart Citation